History of childhood abuse, sensation seeking, and intimate partner violence under/not under the influence of a substance: a cross-sectional study in Russia. - Zhan, Weihai; Shaboltas, Alla V; Skochilov, Roman V; Krasnoselskikh, Tatiana V; Abdala, Nadia (PloS one, 2013)
To examine correlates of perpetration and victimization of intimate partner violence (IPV) under and not under the influence of a substance, we conducted a study among women in Russia.
Keywords: Adolescent; Adult; Adult Survivors of Child Abuse; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Russia; Sexual Behavior; Sexual Partners; Sexually Transmitted Diseases; Spouse Abuse; Substance-Related Disorders; Violence; Women's Health; Young Adult